Assessment of the functional status of patients with rheumatoid arthritis as a result of the physical therapy programme - Nogas, A.; Grygus, I. (Journal of Education, Health and Sport, 2022)
Annotation. A differentiated strategy for the rehabilitation treatment of patients with rheumatoid arthritis is the development and implementation of a comprehensive therapeutic programme that includes the use of non-drug measures in addition to conservative therapy. The purpose of the paper is to evaluate the functional status of patients with rheumatoid arthritis as a result of the proposed physical therapy programme. Materials and methods. A total of 188 patients with rheumatoid arthritis were examined, with an average age of 44.9±7.6 years. All patients were randomly assigned to the control (n=92) and intervention (n=96) groups. Patients in the control group underwent rehabilitation in accordance with the recommendations of the regulatory document of the Ministry of Health of Ukraine. The physical therapy programme for patients of the main group is developed in accordance with the domains of the ICF, taking into account the factors that affect the level of functional impairment, health status and quality of life. The effectiveness of the proposed physical therapy programme on the functional status of patients with rheumatoid arthritis was assessed by the results of the Stanford Health Assessment Questionnaire. Results. At the beginning of the study, the total score for patients in the control group was 6.3±0.7 points and for the intervention group - 6.5±9.5 points. The greatest difficulties arose in getting dressed, including tying laces and fastening buttons, opening and closing a tap, bringing a full cup to the mouth, bending over and picking up an object from the floor. After 3 months, significantly better changes occurred in patients of the main group compared to the control group. So, in the patients of the main group, the total score decreased to 3.9±11.1 points, in the control group this score was worse and amounted to 4.7±2.3 points. After the treatment and physical therapy in 6 months, the functional status of patients in both groups improved, but the total score in the main group was significantly better and closer to normal (1.8±12.2 points) than in patients in the control group (2.9±4.1 points). Significantly better results of functional status indicators in patients of the main group indicate the effectiveness of the proposed physical therapy programme. Conclusion. Increased motor activity in the joints, muscle strength in the affected upper extremities as a result of the proposed physical therapy programme contributed to the improvement of daily activities and functional status of patients in the main group, as evidenced by the results of the Stanford Health Interview. Thus, significantly better changes occurred in the patients of the main group compared to the control group, where conventional rehabilitation treatment was performed.